Violence in health: Causes, effects, and solutions from the perspective of students of a medical school - Tanalı, Gizem; Peker, Ummahan; Çopur, Çağatay; Şahin, Barış Can; Önel, Berivan; Dalgıç, Büşra; Yemez, Rabia; Sünbül, Fevzi; Başaran, Beyza Nur; Gündüz, Nilgün Gamze; Karaosman, Ezgi Naz; Erkaya, Rukiye; et al. (Turkey Health Literacy Journal, 2022)
Purpose: In this study, it is aimed to evaluate the opinion of medical school students towards violence and their views on the cause of violence and solution suggestions.Method: The universe of the study consists of students studying at Hacettepe University Faculty of Medicine in the 2021-2022 academicyear. The data collection form was prepared via Google Forms. The form consists of questions based on personal opinions and experiences and Beck’s Hopelessness Scale. The data collected through the form were transferred to the SPSS program and analyzed. In the analysis process, Kruskal-Wallis, Mann-Whitney U, Spearman correlation tests were used.Results: 421 students were included in the study, of which 48% were preclinical and 52% were clinical. Of the 421 students who participated, 25.2% stated that they had not been exposed to violence but witnessed it, and 5.9% stated that they were exposed to violence. The participants mostly marked the option “Inadequate sanctions against perpetrators” (88.1%) as the reason for violence in health. The solution suggestion most marked by the participants was “Punishing violence with an appropriate punishment” (93.3%).Conclusıon: Violence in health causes hopelessness in medical school students for the future. The issue of violence in health is seriouslyaffected by the media, and according to the opinions of medical school students, fundamental changes should be made and sanctions should be applied to prevent this violence by addressing its causes in different fields, including health literacy.
Keywords: Health; health literacy; violence; medical students; medical staff.